Analisis Risiko Konstruksi Bangunan Gedung Bertingkat Sedang Dengan Metode HIRARC - Reisya Nabila Hasibuan; Syarifah Keumala Intan; Herri Mahyar (Jurnal Serambi Engineering, 2024)
Construction projects are inherently dynamic and entail a certain degree of risk, particularly in the context of the construction of an eight-story building. The occurrence of risks within a project can result in financial losses, necessitating the identification and evaluation of potential risks. In this study, a construction risk analysis was conducted on a medium-rise building comprising eight floors, employing the Hazard Identification, Risk Assessment and Risk Control (Hirarc) method. A quantitative descriptive research study was conducted using a purposive sampling method, with a total of 36 respondents. The primary data were collected in the form of questionnaires, while the secondary data were sourced from Job Safety Analysis (JSA), K3 audit reports, and plan drawings. The quantitative descriptive questionnaire instrument was found to be valid and reliable. The results of the hazard identification process, based on data obtained from secondary sources, identified 45 potential risks. These were then subjected to a risk assessment based on probability and severity. The risk assessment results indicate that there is one high-risk activity, namely the modification of the structural design of the columns, beams, and floor plates. Additionally, there are 44 risks classified as moderate-risk. The most effective risk control strategy from an engineering perspective is to implement a flexible material procurement schedule, which facilitates improved communication and coordination. From an administrative standpoint, monitoring and evaluation represent key risk control measures.